2020
DOI: 10.1021/acsami.0c07419
|View full text |Cite
|
Sign up to set email alerts
|

Heat-Generating Iron Oxide Multigranule Nanoclusters for Enhancing Hyperthermic Efficacy in Tumor Treatment

Abstract: The development of heat-generating magnetic nanostructures is critical for the effective management of tumors using magnetic hyperthermia. Herein, we demonstrate that polyethylene glycol (PEG)-coated iron oxide (magnetite, Fe3O4) multigranule nanoclusters (PEG-MGNCs) can enhance the efficiency of hyperthermia-based tumor suppression in vitro and in vivo. MGNCs consisting of granules (crystallites) measuring 22.9 nm in diameter were prepared via the hydrothermal polyol method, followed by the surface modificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…Jeon et al studied the in vivo efficacy of magnetic hyperthermia induced with PEG-coated iron oxide multigranule nanoclusters (PEG-MGNCs) compared to PEGylated single iron oxide nanoparticles (PEG-NPs) in SCC7 (mouse squamous cell carcinoma) tumour-bearing mice. 99 The AMF stimulation (19.5 kA/m, 389 kHz) was induced after 24 and 48 h from nanoparticles injection and lasted 30 min. As can be seen from Figure 4.a, at the end of the stimulus, the temperature of the tumour tissue treated with PEG-MGNCs reached ≈ 45°C.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…Jeon et al studied the in vivo efficacy of magnetic hyperthermia induced with PEG-coated iron oxide multigranule nanoclusters (PEG-MGNCs) compared to PEGylated single iron oxide nanoparticles (PEG-NPs) in SCC7 (mouse squamous cell carcinoma) tumour-bearing mice. 99 The AMF stimulation (19.5 kA/m, 389 kHz) was induced after 24 and 48 h from nanoparticles injection and lasted 30 min. As can be seen from Figure 4.a, at the end of the stimulus, the temperature of the tumour tissue treated with PEG-MGNCs reached ≈ 45°C.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…(b6) Tumor changes in mice before and after MH. Adapted with permission from ref . Copyright 2020 American Chemical Society.…”
Section: Biomedical Applications Of Micronanoswarmsmentioning
confidence: 99%
“…Jeon et al . developed iron oxide nanoparticle-based swarms coated with polyethylene glycol for tumor MH in vivo . As shown in Figure b6, it can be found that the tumor growth was suppressed after the swarms were heated under MH from the differences of tumor volume in mice.…”
Section: Biomedical Applications Of Micronanoswarmsmentioning
confidence: 99%
“…Integration of magnetic iron oxide (Fe 3 O 4 ) and Au NPs can be used in hyperthermia [ 10 ], catalysis [ 11 ], and surface modification [ 12 ]. Furthermore, Fe 3 O 4 NPs have been used as carriers for cell imaging [ 13 ] and drug delivery systems [ 14 ] due to their apparent superparamagnetism, high specific surface area, significant colloidal stability, and excellent biocompatibility [ 15 , 16 ]. An Au coating onto magnetic NPs is another appealing hybrid system [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%